Association between laboratory capacities and world-cup performance in Nordic combined - Rasdal, V.; Fudel, R.; Kocbach, J.; Moen, F.; Ettema, G.; Sandbakk, O. (PLOS ONE, 2017)
Background: Nordic combined (NC) is an Olympic winter-sport performed as a ski jumping (SJ) event followed by a cross-country (XC) pursuit race employing the skating style. Purpose: To elucidate the associations between sport-specific laboratory capacities and SJ, XC skiing, and overall NC performance in a world-cup NC event. Methods: Twelve international world-cup NC athletes from 8 nations performed laboratory testing one day prior to participating in a world-cup NC event. Squat jumps and SJ imitations (IMIT) were performed on a three-dimensional force plate, whereas XC skiing-specific physiological characteristics were obtained from roller ski skating tests on a treadmill and an all-out double poling (DP) test. Finally, body composition was measured. Laboratory capacities were correlated against performance in SJ, 10-km XC skiing, and overall NC in the world-cup event. Multiple regression analysis was used to determine the best suited laboratory variables for predicting performance. Results: Vertical IMIT velocity together with body-mass provided the best prediction for SJ performance (r2 = 0.70, p<0.01), while body-mass-normalized and DP power provided the best prediction for XC performance (r2 = 0.68, p<0.05). Body-mass-normalized was the only significant correlate with overall NC performance (r2 = 0.43, p<0.05) in this competition. Conclusion: Overall, the concurrent development of , upper-body power, and SJ-specific vertical jump capacity while minimizing body-mass within the BMI limit set by FIS should be considered in the seasonal training of NC athletes.